2010
DOI: 10.1002/jid.1757
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Burden of Liberalisation: The Impact of India's Economic Reforms on Its Female Agricultural Labour

Abstract: India has experienced unprecedented growth in the last two decades-a development largely attributed to economic reforms initiated in the early 1990s. India's approach to liberalisation has been commended for its gradual implementation and its sympathy for poor rural workers. Studies examining the relevance of this claim generally use national survey data, which are seriously limited. So far little effort has been focussed on understanding what reforms actually mean for the rural poor using primary data. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Rawal and Saha (2015) observe that supporters of economic liberalization see women's increased labour force participation as evidence of economic empowerment while critics attribute an increase in women's participation to agrarian crisesin particular those associated with unprofitable crop production and distress migration (see Kanchi 2010); Kelkar and Wang 2007;Srivastava (2011). Numerous micro-studies document the out-migration of males from agriculture to other sectors and the implications of out-migration for leftbehind women (see Hardikar 2004;Garikipati 2006;Garikipati and Pfaffenzeller 2012). Hardikar's (2004) study in two villages of Madhya Pradesh found that the migration of menmostly from marginal and small land-holding groupsput further pressure on women and forced some women cultivators to abandon their farms.…”
Section: Women In Agriculture: Evidence From Past Studiesmentioning
confidence: 99%
“…Rawal and Saha (2015) observe that supporters of economic liberalization see women's increased labour force participation as evidence of economic empowerment while critics attribute an increase in women's participation to agrarian crisesin particular those associated with unprofitable crop production and distress migration (see Kanchi 2010); Kelkar and Wang 2007;Srivastava (2011). Numerous micro-studies document the out-migration of males from agriculture to other sectors and the implications of out-migration for leftbehind women (see Hardikar 2004;Garikipati 2006;Garikipati and Pfaffenzeller 2012). Hardikar's (2004) study in two villages of Madhya Pradesh found that the migration of menmostly from marginal and small land-holding groupsput further pressure on women and forced some women cultivators to abandon their farms.…”
Section: Women In Agriculture: Evidence From Past Studiesmentioning
confidence: 99%
“…Several analyses of developing-country agricultural resources back up the IMF's concerns. According to Garikipati and Pfaffenzeller (2012), the agricultural labor force in developing nations is comprised of unskilled employees, particularly underpaid or unpaid women. Kannan (2015) shows in his analysis of crop performance and agricultural expenses and revenue for developing nations that, despite a considerable increase in agricultural income from 1981-1982 to 2007-2008, farm employees' actual pay grew only modestly.…”
Section: Resultsmentioning
confidence: 99%
“…Research from South Asia suggests nuanced effects of the feminization of agriculture on women, complicated by differences in the mechanism of feminization, household status, and socioeconomic status. Studies demonstrate that women-particularly poor women-are bearing the brunt of the heavy workloads, instability, risk, and psychological stress of agricultural livelihoods, without radical or sustained increases in agency and empowerment (Adhikari and Hobley 2015;Bhandari and Chinnappa Reddy 2015;Garikipati and Pfaffenzeller 2012). Women entering agricultural wage work generally lack resources and opportunities to pursue alternative livelihoods, largely due to limited formal education, and these jobs have not only low pay but also low status (Garikipati 2008;Pattnaik et al 2018;Srivastava and Srivastava 2010).…”
Section: Mechanisms Causes and Effects Of The Feminization Of Agricul...mentioning
confidence: 99%